Personal Love - Grabowski, Marian (Filozofia Chrześcijańska, 2014)
This paper presents the concept of personal love in the Bible according to Nicolai Hartmann and Max Scheler. On this background the notion of sexual love as personal love according to Karol Wojty³a is discussed.